1990
DOI: 10.1007/bf00315424
|View full text |Cite
|
Sign up to set email alerts
|

Dosage prescribing and plasma oxipurinol levels in patients receiving allopurinol therapy

Abstract: This study examined dosage prescribing patterns and steady-state oxipurinol plasma concentrations in 66 patients receiving chronic allopurinol therapy. Most patients (65%) were taking 300 mg allopurinol daily, although renal impairment was common. Using published guidelines, it was estimated that 35% of patients were receiving excessive dosages of allopurinol. Consequently, the plasma oxipurinol concentrations were often very high (mean (SD) was 156 (109) mumol.l-1). Accumulation of oxipurinol was inversely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…Allopurinol, which is a specific inhibitor of xanthine oxidase [32], totally inhibited isovanillic acid formation. This is in accordance with the kinetic studies, where isovanillin was found to be a substrate of xanthine oxidase [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allopurinol, which is a specific inhibitor of xanthine oxidase [32], totally inhibited isovanillic acid formation. This is in accordance with the kinetic studies, where isovanillin was found to be a substrate of xanthine oxidase [7].…”
Section: Discussionmentioning
confidence: 99%
“…The medium was oxygenated with 95% O 2 /5% CO 2 initially and every subsequent hour for 5 min, which was sufficient to maintain optimum metabolite production. Incubations with freshly prepared liver slices were also performed in the presence of the inhibitors, allopurinol for xanthine oxidase activity [32] and disulfiram for aldehyde dehydrogenase activity [33,34]. Aliquots (0.2 ml) were removed at various time intervals, treated with 0.1 ml of 3.6% perchloric acid, centrifuged for 2.5 min at maximum speed on a Beckman microfuge B and the supernatant was analyzed by HPLC.…”
Section: Metabolism Of Isovanillin With Freshly Prepared and Cryopresmentioning
confidence: 99%
“…Incubations with freshly prepared liver slices were also performed in the presence of inhibitors. The inhibitors used were isovanillin for aldehyde oxidase activity [13,14], allopurinol for xanthine oxidase activity [29] and disulfiram for aldehyde dehydrogenase activity [30,31]. Aliquots (0.2 ml) were removed at t= 0 min and at various time intervals, added to 0.1 ml of 3.6 % perchloric acid and centrifuged for 2.5 min at maximum speed on a Beckman microfuge B.…”
Section: Incubation Conditions With Liver Slicesmentioning
confidence: 99%
“…Homovanillamine incubations with freshly prepared liver slices were also performed in the presence of the inhibitors, isovanillin for aldehyde oxidase [6,7], allopurinol for xanthine oxidase [26] and disulfiram for aldehyde dehydrogenase activity [27,28]. For comparison reasons, the results on the effect of inhibitors in freshly prepared liver slices have been normalized per 100 mg of liver.…”
Section: Incubation Conditions With Freshly Prepared and Cryopreservementioning
confidence: 99%